Conventional Synthetic Disease-Modifying Anti-rheumatic Drugs for Psoriatic Arthritis: Findings and Implications From a Patient Centered Longitudinal Study in Brazil - Faria, Ronaldo José; Cordeiro, Francisca Janiclecia Rezende; dos Santos, Jéssica Barreto Ribeiro; Alvares-Teodoro, Juliana; Guerra Júnior, Augusto Afonso; Acurcio, Francisco de Assis; da Silva, Michael Ruberson Ribeiro (Frontiers in Pharmacology, 2022)
Background: Conventional synthetic disease-modifying antirheumatic drugs are the first-line treatment to inhibit the progression of psoriatic arthritis. Despite their widespread clinical use, few studies have been conducted to compare these drugs for psoriatic arthritis. Methods: a longitudinal study was carried out based on a centered patient national database in Brazil. Market share of drugs, medication persistence, drug costs, and cost per response were evaluated. Results: a total of 1,999 individuals with psoriatic arthritis were included. Methotrexate was the most used drug (44.4%), followed by leflunomide (40.6%), ciclosporin (8.2%), and sulfasalazine (6.8%). Methotrexate and leflunomide had a greater market share than ciclosporin and sulfasalazine over years. Medication persistence was higher for leflunomide (58.9 and 28.2%), followed by methotrexate (51.6 and 25.4%) at six and 12 months, respectively. Leflunomide was deemed the most expensive drug, with an average annual cost of 317.25, followed by sulfasalazine (106.47), ciclosporin (97.64), and methotrexate (40.23). Methotrexate was the drug being the lowest cost per response. Conclusion: Methotrexate had the best cost per response ratio, owing to its lower cost and a slightly lower proportion of persistent patients when compared to leflunomide. Leflunomide had a slightly higher medication persistence than methotrexate, but it was the most expensive drug.